2015
DOI: 10.1016/j.jphs.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-reovirus activity of kuraridin isolated from Sophora flavescens against viral replication and hemagglutination

Abstract: In this study, we evaluated the anti-reovirus activity of kuraridin isolated from the roots of Sophora flavescens. In particular, we focused on whether this property is attributable to direct inhibition of reovirus attachment and/or inhibition of viral replication with the aid of time-of-addition (pre-treatment, simultaneous treatment, and post-treatment) experiments. No significant antiviral activity of kuraridin was detected in the pre-treatment assay. In the simultaneous assay, the 50% effective inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Genipin also suppressed rotavirus replication at two distinct stages of the viral replication cycle: the rotavirus RNA replication cycle in MA104 cells was significantly inhibited at the early stage in pre-treatment and the late stage in post-treatment. These results are supported by previous studies, which indicated that kuraridin isolated from Sophora flavescens and iridoid glycosides extracted from Fructus Gardeniae have inhibited reovirus and influenza virus by replication cycles in pre-and post-treatment 37,38 . Additionally, genipin showed viricidal effects against rotavirus.…”
Section: Discussionsupporting
confidence: 89%
“…Genipin also suppressed rotavirus replication at two distinct stages of the viral replication cycle: the rotavirus RNA replication cycle in MA104 cells was significantly inhibited at the early stage in pre-treatment and the late stage in post-treatment. These results are supported by previous studies, which indicated that kuraridin isolated from Sophora flavescens and iridoid glycosides extracted from Fructus Gardeniae have inhibited reovirus and influenza virus by replication cycles in pre-and post-treatment 37,38 . Additionally, genipin showed viricidal effects against rotavirus.…”
Section: Discussionsupporting
confidence: 89%
“…The MIC of Kuradin against all isolates was 48 µg/mL which is more or less similar to the value of 50 µg/mL reported for S. aureus [ 55 ], but higher than a value of 20 µg/mL previously reported for different bacteria [ 35 ]. Kuraridin, from Sophora flavescens , has been previously reported as a potential antimicrobial compound [ 35 , 36 , 56 ]. The MIC of emodin against C. jejuni was 50 µg/mL, which is slightly lower than the 70–90 µg/mL previously reported for P. aeruginosa and S. aureus [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clove oil and its major phytochemical eugenol are known for their antimicrobial and virulence-modulating activities against Campylobacter species [ 28 , 33 ]. Emodin has been found to inhibit Pseudomonas aeruginosa [ 34 ], while kuraridin had activity against different pathogenic bacteria [ 35 ] and reoviruses [ 36 ]. Cinnamaldehyde has been reported to possess antimicrobial properties against various pathogens [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Xinjiang Chinese Herbal Medicine Handbook has reported that it exerts detoxification, pain relief, and insecticidal effects. Local people use it to treat dysentery, stomachache, leucorrhea disorder, eczema, psoriasis, and so on (Huang, Wang, Zhu, Zhang, & Zhang, ; Iinuma et al, ; Krishna, Rao, & Banji, ; Kwon, Basnet, et al, ; Ruangrungsi et al, ; Toda & Shirataki, ).…”
Section: Introductionmentioning
confidence: 99%